2020
DOI: 10.1159/000509748
|View full text |Cite
|
Sign up to set email alerts
|

Crohn’s versus Cancer: Comparison of Functional and Surgical Outcomes after Right-Sided Resections

Abstract: Background: The objective of this study was to compare functional and surgical outcomes of patients undergoing ileocecal resection for Crohn’s disease (CD) to patients undergoing oncological right colectomy. Methods: Retrospective single-center cohort study including consecutive patients undergoing right colectomy for adenocarcinoma (oncological resection) or CD (mesentery-sparing resection) between July 2011 and November 2017. Outcome measures were pathological details (lymph node yield), postoperative recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…ERAS might be an effective protocol after IBD surgery. The reduction in hospital stay brings cost savings and reduces the lost work time of family members, improves patient comfort and reduces exposure to hospital-acquired infections at the same time[ 17 ]. Moreover, the likelihood anastomotic fistula was significantly reduced in the ERAS group, which confirmed the safety of the ERAS protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ERAS might be an effective protocol after IBD surgery. The reduction in hospital stay brings cost savings and reduces the lost work time of family members, improves patient comfort and reduces exposure to hospital-acquired infections at the same time[ 17 ]. Moreover, the likelihood anastomotic fistula was significantly reduced in the ERAS group, which confirmed the safety of the ERAS protocol.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies suggest the feasibility of ERAS for IBD patients[ 16 ]; however, work comparing the efficiency of ERAS in IBD and non-IBD patients is scant[ 17 ]. Therefore, the purpose of this meta-analysis was to evaluate the safety and efficacy of ERAS in IBD surgery.…”
Section: Introductionmentioning
confidence: 99%
“…There are ongoing randomized trials, but with respect to safety, it has recently been shown that there does not appear to be any significant difference in functional or surgical outcomes after ICR for CD vs colon cancer operations. 12…”
Section: Discussionmentioning
confidence: 99%
“…There are ongoing randomized trials, but with respect to safety, it has recently been shown that there does not appear to be any significant difference in functional or surgical outcomes after ICR for CD vs colon cancer operations. 12 Critics of the EME approach have properly pointed out that care must be taken to preserve the vascularity, and length, of the proximal small intestine. 9 Experienced surgeons are familiar with handling the severely inflamed, friable, thickened mesenteric often seen in CD.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence suggests that ERP can improve short-term clinical outcomes immediately after abdominal surgery in patients with IBD (231,232,233,234,235,236,237,238,239,240,241,242,243,244,245,246), and only two studies have mentioned multidisciplinary evaluation and planning prior to discharge (237,242).…”
Section: Accepted Manuscriptmentioning
confidence: 99%